Evaluation of the Utilization of the Hospital Management Information System (SIMRS) at Madani Regional General Hospital, Palu - Muhammad Rifial; Amran Razak; Darmawansyah Darmawansyah; Indar Indar; Arsyad Rahman (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: The Hospital Management Information System (SIMRS) plays a crucial role in supporting optimal healthcare services in hospitals. SIMRS enables efficient and effective management of information, ranging from patient data to hospital administration. At Madani Regional General Hospital, Palu, the implementation of SIMRS has been carried out; however, operational challenges and user satisfaction issues still need to be evaluated. This study aims to evaluate the utilization of SIMRS at Madani Regional General Hospital, Palu, in 2024, and to analysed the impact of system usage, user satisfaction, information quality, and service quality on the net benefits of SIMRS. Methods: This study uses a quantitative method with a cross-sectional study approach and logistic regression analysis. The population of this study includes all employees at Madani Regional General Hospital, Palu. The sample consists of 172 respondents, determined using the Slovin formula Results: The study shows that system usage (p = 0.007), user satisfaction (p = 0.003), information quality (p = 0.002), and service quality (p = 0.006) are associated with the utilization of SIMRS at Madani Regional General Hospital, Palu. Based on Binary Logistic analysis, the variable with the strongest influence is System Usage (Sig = 0.006) Conclusion: This study concludes that the use of SIMRS at Madani Regional General Hospital, Palu, provides significant benefits in terms of hospital service efficiency and effectiveness. System usage is the most dominant factor influencing the utilization of HMIS, followed by user satisfaction, information quality, and service quality. It is recommended to continuously improve the quality of system usage by providing ongoing training for hospital staff.